(untitled) (Swiss Medical Weekly, 2021)
A 66-year-old man presented with 4 weeks of bilateral buttock pain without previous trauma or intense exercise. He had been treated with immune checkpoint inhibitors because of metastasising melanoma and experienced immune-related adverse events requiring treatment with corticosteroids. Magnetic resonance imaging of the pelvis revealed bilateral avulsion of the proximal hamstring muscles. Treatment with physical therapy and nonsteroidal anti-inflammatory drugs led to a slow but lasting relief. This is, to our knowledge, the first report of symptomatic non-traumatic bilateral hamstring muscle avulsion following treatment with immune checkpoint inhibitors and corticosteroids.